ANALISIS KEMAMPUAN MULTIREPRESENTASI MAHASISWA PENDIDIKAN FISIKA SEMESTER II TENTANG KONSEP SINAR MONOKROMATIS - arita fajar damasari; Sudarti sudarti (Faktor Jurnal Ilmiah Kependidikan, 2021)
Multi-representation is an integral part of the representation of science, especially physics. This study analyzes and evaluates the ability of physics education students regarding monochromatic rays. The research method used is the descriptive method with  40 respondents second semester of the physics education study program. The analysis was generated based on a questionnaire consisting of 8 verbal and picture questions that were answered correctly. The study resulted in a higher percentage of verbal multi-presentation abilities than picture multi-presentation. The value of verbal multi-representation presentation is 94.06% and picture multi-representation is 53.55 and the difference between the two is 40.51%. Further research is needed on appropriate learning methods to improve students' multi-representation abilities of images on monochromatic light material.